Isolation, identification and antibacterial activity of endophytes from the seeds of Panax japonicus - Jin, Rui; Tang, Tingting; Huang, Xilun; Huang, Juan; Liang, E.; Zhang, Lai (PLOS ONE, 2025)
The purpose of this study is to isolate and identify endophytes from the seeds of Panax japonicus, find growth-promoting endophyte that favors seed germination in P. japonicus, and provide theoretical reference for further research on the effect of endophytes on seed germination. Methods The streak plate method isolated the endophytic bacteria from the seeds. The isolated endophytes were identified by morphology, ITS and 16S rDNA sequence analysis. The antibacterial activity of the isolated endophytes and their metabolites was studied by disk method. Results The seed was disinfected with 75% alcohol for 30s and 1% HgCl2 for 9 min, and the contamination rate was the lowest (3.33%). Seven endophytic fungi strains were isolated from the seeds of P. japonicus, named PjZ1, PjZ2, PjZ3, PjZ4, PjZ5, PjZ6, and PjZ7, respectively, four strains belonged to the genus Fusarium tricinctum, one to Fusarium reticulatum, one to Fusarium sarcochroum, and one to Alternaria alternata; Three strains of endophytic bacteria were isolated and named PjX1, PjX2 and PjX3, respectively. After morphological observation and 16S rDNA gene sequencing, two strains belong to the genus Enterobacteriaceae bacterium and one belongs to the genus Pseudomonas sp. Among the endophytic fungi strains isolated, only PjZ4 showed significant bacteriostatic activity against Escherichia coli, PjZ3, PjZ4, PjZ5 and PjZ7 had antibacterial activity against Bacillus subtilis, and none of the 7 strains had antibacterial activity against Staphylococcus aureus. It was found that the metabolites of 7 endophytic fungi and 3 endophytic bacteria had no antibacterial activity. Conclusion In this study, we investigated the method of P. japonicus seed disinfection, and the results showed that 75% alcohol disinfection for 30s and 1% HgCl2 disinfection for 9 min resulted in the lowest contamination rate of 3.33%, in which the greatest influence on the seed disinfection effect was the concentration of HgCl2. Meanwhile, 10 endophyte species of P. japonicus seeds were isolated and identified, Fusarium spp. and Alternaria alternata. were not the dominant species in the growth and development process of P. japonicus while Enterobacteriaceae and Pseudomonas sp. were the growth-promoting endophyte in the promotion of plant growth and development, and provide a theoretical reference for further research on the biological functions and active substances of endophyte in the seeds of P. japonicus.